Research Paper: Producing High Average Power Pulses From the Yb:YAG Thin-disk Active Medium with Acousto-optic Modulator - Kaveh Pasandideh; Ahmad Moshaii; Saeid Radmard; Tahereh Namdari (فیزیک کاربردی ایران)
In recent years, thin-disk active media geometry has facilitated the development of pulsed and continuous laser sources with extremely high output powers. In this study, the technique of Q-switching utilizing an acousto-optic modulator and a Yb: YAG thin-disk active medium was employed to produce high average power and high repetition rate pulses at a wavelength of 1030 nm. The characteristics of output pulses, including time duration, single pulse energy, and average power were measured and analyzed at different pump levels and repetition rates. Depending on the pump level, the fabricated laser operated stably in the repetition range from 0.5 to 9 kHz. The time duration of the output pulses using this approach was approximately one microsecond. Moreover, the output pulse with the maximum energy above 50 mJ and also the maximum average output power of 340 watts was obtained from this laser. Also, the findings indicated that the repetition rate does not significantly affect the output pulse energy at higher pump powers.